FEATURES OF PHONETIC ADAPTATION AFTER PROSTHETICS WITH COMPLETE DENTURES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Removable dentures are perceived as irritants that cause a response of a compensatory-adaptive nature. This review attempts to summarize and systematize possible factors contributing to the adaptation of patients' phonetics to removable dentures. Phonetic adaptation to removable dentures is a complex process that depends on various factors, the most significant of which are the functional quality of the denture and the patient’s motivation to use the denture.